Evaluation of flavor & aroma compounds during fermentation of coconut (Cocos nucifera Linn.) sap with tanbark. - Superioridad, Elton Albancia
There are different types of product that can be produced from the coconut (Cocos nucifera Linn.) sap, including tuba (coconut toddy). In order to extend shelf-like of tuba, baluk (tanbark) is commonly added. Evaluation of naturally fermented tuba added with baluk obtained from Brgy. Baras, Guimbal, Iloilo. Philippines was carried out to establish the volatile compounds responsible for the distinct flavor and aroma of the fermented alcoholic beverage. Tuba with baluk was fermented naturally for 24 hours and was evaluated at 3 fermentation periods, namely 0-3 hours, 8-11 hours, and 21-24 hours after sample collection for its sensorial attributes (flavor and aroma), volatile compounds, and physicochemical properties (titrable acidity, pH, total soluble solids, and alcohol content). The evaluation for volatiles was done using headspace-solid phase microextraction gas chromatograhy-mass spectrometry (HS-SPME GC-MS). The sample was found contain 20 volatile compounds that may be categorized as alcohols, esters, carboxyllic acids, and others (phenol, amines, and amides). These compounds are by-products of microbial activities and chemical reactions during fermentation and affects the sensorial properties of tuba with baluk. Esters, which is associated with sweet, fruity and floral aroma of the sample, were found to be the predominant aromatic volatile compounds detected and contributed to the flavor perceived by more than 50% of the trained panelists who evaluated the sample. Alcohols were found to contribute to the bitter to sweet taste and floral to fruity aroma. Amines, amides and phenol were found to impart bitter taste and resinous, woody to nutty aroma. Carboxyllic acids were found to contribute sour, astringent, bitter, and vinegar-like flavor and indicates spoilage of the sample. Tuba with baluk has titrable acidity (TA) range of 0.345-0.512%, a decreasing pH of 3.74-3.58, a reduction in total soluble solids (TSS) from 10.63-4.820Brix, and alcohol content ranging from 4.90-7.36%. One-Way ANOVA at α = 0.05 revealed that there were significant differences among the physicochemical properties of tuba with baluk at different fermentation periods after sampling. This study showed that fermentation of tuba with baluk resulted to perceptible changes in the flavor and aroma. Liewise, changes in relative peak areas of volatile compounds were detected by HS-SPME GC-MS. Generally, it can be concluded that the changes in the relative peak areas of detected volatiles can be used as markers to identify quality of tuba with baluk during fermentation.